Mulheres vítimas de violência doméstica: como mudar essa realidade? - Balsamo, Sérgio Leão (2019)
Explicitly or veiled domestic violence against women occurs in many households, causing various disorders arising from the traumatic situation. It can take on different configurations, from assaults that can lead to death, to the subtlest forms of psychic torture that cause panic and destroy the victims' self-esteem, causing them to live and face uncountable difficult situations. The aims of this study is to identify the forms of violence suffered by the participants, to determine the scenario and consequences of such violence, to identify the forms of protection accessed, to recognize signs of posttraumatic stress disorder , to propose preventive measures and to improve posttraumatic stress . It is a descriptive, biographical research with qualitative approach with content analysis by thematic categorization. Ten women victims of domestic violence were interviewed. Data collection was conducted through oral interview, guided by this triggering question: “Tell me the story about the aggression you suffered" and application of sociodemographic forms. The age of participants ranged from 28 to 52 years, most of whom had finished high school (5) and were working at the time of the interview (7). The narratives were categorized into four themes and respective sub-themes : forms of violence ( physical, psychological, sexual, moral , patrimonial), violence scenario (absence of support, aggressor’s behaviour, disputes, victim blame, invisibility of violence) , protection of the victim ( institutional support, family support, school / work support, shelter, self-help) and impacts of violence ( feelings, PTSD signal, fear, losses, collateral damage , victim reactions) . All participants underwent physical and psychological violence, 7 reported financial abuse, 4 suffered sexual violence, 2 suffered moral violence. All of the patients had signs of PTSD, and the most common were intense fear, guilt and isolation, difficulty in maintaining routine at home and work, as well as having another affective relationship. The therapeutic action should focus on the emotional distress caused by violence and not on the social context in which these women live. Primary health care can make a difference by providing specific and appropriate policy actions to this population aiming at the integrity of human beings, health promotion, prevention of aggravations and emphasis on intersectionality